Prescription Patterns for Tigecycline in Severely Ill Patients for Non-FDA Approved Indications in a Developing Country: A Compromised Outcome - Moghnieh, Rima A.; Abdallah, Dania I.; Fawaz, Ismail A.; Hamandi, Tarek; Kassem, Mohammad; El-Rajab, Nabila; Jisr, Tamima; Mugharbil, Anas; Droubi, Nabila; Al Tabah, Samaa; Sinno, Loubna; Ziade, Fouad; et al. (Frontiers in Microbiology, 2017)
Introduction: With the rise in antibiotic resistance, tigecycline has been used frequently in off-label indications, based on its in-vitro activity against multidrug-resistant organisms. In this study, our aim was to assess its use in approved and unapproved indications. Materials and Methods: This is a retrospective chart review evaluating a 2-year experience of tigecycline use for > 72 hours in 153 adult patients inside and outside critical care unit from January 2012 to December 2013 in a Lebanese tertiary-care hospital. Results: Tigecycline was mostly used in off-label indications (81%) and prescribed inside the critical care area, where the number of tigecycline cycles was 16/1000 patient days. Clinical success was achieved in 43.4% of the patients. In the critically ill group, it was significantly higher in patients with a SOFA score < 7 using multivariate analysis (Odds Ratio (OR)= 12.51 [4.29 – 36.51], P<0.0001). Microbiological success was achieved in 43.3% of patients. Yet, the univariate and adjusted multivariate models failed to show a significant difference in this outcome between patients inside vs. outside critical care area, those with SOFA score < 7 vs. ≥ 7, and in FDA-approved vs. off-label indications. Total mortality reached approximately 45%. It was significantly higher in critically ill patients with SOFA score ≥ 7 (OR= 5.17 [2.43 - 11.01], P<0.0001) and in off-label indications (OR= 4.00 [1.30 - 12.31], P=0.01) using an adjusted multivariate model. Gram-negative bacteria represented the majority of the clinical isolates (81%) and Acinetobacter baumannii predominated (28%). Carbapenem resistance was present in 85% of the recovered Acinetobacter, yet, more than two third of the carbapenem-resistant Acinetobacter species were still susceptible to tigecycline. Conclusion: In our series, tigecycline has been mostly used in off-label indications, specifically in severely ill patients. The outcome of such infections was not inferior to that of FDA-approved indications, especially inside critical care area. The use of this last resort antibiotic in complicated clinical scenarios with baseline microbiological epidemiology predominated by extensively-drug resistant pathogens ought to be organized.